Gradual approach to refinement of the nasal tip: surgical results - Carvalho,Thiago Bittencourt Ottoni de (2015)
Introduction: The complexity of the nasal tip structures and the impact of surgical maneuvers make the prediction of the final outcome very difficult. Therefore, no single technique is enough to correct the several anatomical presentations, and adequate preoperative planning represents the basis of rhinoplasty. Objective: To present results of rhinoplasty, through the gradual surgical approach to nasal tip definition based on anatomical features, and to evaluate the degree of patient satisfaction after the surgical procedure. Methods: Longitudinal retrospective cohort study of the medical charts of 533 patients of both genders who underwent rhinoplasty from January of 2005 to January of 2012 was performed. Cases were allocated into seven groups: (1) no surgery on nasal tip; (2) interdomal breakup; (3) cephalic trim; (4) domal suture; (5) shield-shaped graft; (6) vertical dome division; (7) replacement of lower lateral cartilages. Results: Group 4 was the most prevalent. The satisfaction rate was 96% and revision surgery occurred in 4% of cases. Conclusion: The protocol used allowed the implementation of a gradual surgical approach to nasal tip definition with the nasal anatomical characteristics, high rate of patient satisfaction with the surgical outcome, and low rate of revision.